2022
DOI: 10.19166/jstfast.v6i1.5284
|View full text |Cite
|
Sign up to set email alerts
|

Pemanfaatan Tepung Daun Singkong sebagai Substitusi Tepung Terigu dalam Pembuatan Kukis [Utilization of Cassava Leaves Flour as Wheat Flour Substitute in the Making of Cookies]

Abstract: <p><em>Cookies are a product commonly made from wheat flour as the main ingredient and widely consumed by people. However, gluten in wheat flour can cause allergies, so the consumption of wheat-based products is limited. Furthermore, cookies also have low levels of protein and dietary fibre. Therefore, it is necessary to find another raw materials as an alternative in the making of cookies. In this research, wheat flour substituted with cassava leaves flour in various ratios (100:0; 90:10; 80:20; 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
2
0
2
Order By: Relevance
“…Menurut Pusuma dkk (2018) hal tersebut dikarenakan peningkatan substitusi tepung ampas kelapa dapat mengurangi jumlah protein gluten yang terdapat dalam adonan, sehingga tekstur yang dihasilkan tidak sebaik dengan roti tawar 100% terigu. Hal ini sesuai dengan penelitian yang dilakukan oleh (Soedirga, 2021) bahwa semakin banyak penambahan bahan yang mengandung serat tinggi, maka tekstur pada produk akan semakin keras.…”
Section: Teksturunclassified
“…Menurut Pusuma dkk (2018) hal tersebut dikarenakan peningkatan substitusi tepung ampas kelapa dapat mengurangi jumlah protein gluten yang terdapat dalam adonan, sehingga tekstur yang dihasilkan tidak sebaik dengan roti tawar 100% terigu. Hal ini sesuai dengan penelitian yang dilakukan oleh (Soedirga, 2021) bahwa semakin banyak penambahan bahan yang mengandung serat tinggi, maka tekstur pada produk akan semakin keras.…”
Section: Teksturunclassified
“…Peningkatan persentase konsumsi kukis ini juga terjadi pada tahun 2020 sebesar 4,25% dibandingkan tahun sebelumnya (BPS, 2020). Tepung terigu sebagai bahan baku dalam pembuatan kukis memiliki gluten, namun keberadaan gluten dapat menyebabkan alergi pada beberapa kalangan sehingga konsumsi produk berbasis tepung terigu menjadi terbatas (Soedirga et al, 2021).…”
Section: Pendahuluanunclassified
“…Several previous studies have revealed several local flours from leaves that can replace wheat flour as raw material for cookies, including the substitution of moringa leaf flour (Moringa oleifera L.) in cookies for physical properties, organoleptic properties, proximate levels, and Fe levels [11], the use of cassava leaf flour as a substitute for wheat flour in making cookies [12], the development of a cookie product as a substitute for katuk (Sauropus androgynus (L.) leaf flour and green beans for nutritional content and organoleptic testing as disaster emergency food for breastfeeding mothers [13], variations in mixing soursop leaf flour (Annona muricata Linn) in making cookies in terms of physical properties, organoleptic properties and fiber content [14]. The effect of substituting wheat flour with modified white sweet potato flour (Ipomoea batatas L.) and adding pandan flour (Pandanus amaryllifolius) on the quality of cookies using the creaming method [15].…”
Section: Introductionmentioning
confidence: 99%